THE EFFECTS OF OBESITY ON THE ACTIVE PHASE OF THE FIRST STAGE OF LABOR - Mahmood, Dekan Kamaran; Khalil, Rozhan Yassin (Journal of Sulaimani Medical College, 2022)
Background Obesity is carrying many pregnant women now a day and has many risks for complications. There is an association between body mass index and the progression of the active phase of first-stage labor. Objectives To estimate and detect obesity’s effect on the duration and progression of the active phase of labor and the outcomes of the deliveries, either by vaginal delivery or cesarean section. Patients and Methods A prospective observational cross-sectional study was designed and conducted at Sulaimani maternity teaching hospital in Sulaimani City. From 1st February 2020 to 1st February 2021, about labor study included the progression of 184 multiparous women (para1-4) with a single vertex presentation from (37+1 to 41+6) weeks of complete gestation. Either by spontaneous or induction labor (misoprostol or oxytocin). Between four groups, defined by body mass index according to the world health organization. Normal (n=88), over weight (n=3), obesity class 1(n=43), obesity class 2(n=50) Results A total of 184 patients were collected in this study. The mean ± SD (standard deviation) age/year of participants was (27, 49 ±5.54 SD) minimum age was 17 years, and the maximum age was 44 years. A high percentage of them (51.6%) were living in urban. About (27.2%) were classified as obesity class 2, which carries a high percentage of cases that ends by cesarean section C/S (n=9) 81.8%, with prolonged duration of active phase by mean (4.988) and standard deviation (1.9302) in comparison with other classes. Conclusion The duration of the active phase of labor, cesarean section rate, and the time for induction until the active phase of labor were increased by increasing body mass index.
Keywords: Maternal obesity; Active phase of first stage labor; Cesarean section; vaginal delivery